Bioética, vulnerabilidades e participação social na avaliação de tecnologias em saúde: uma leitura das decisões da CONITEC em doenças raras - Hanshkov, Viviane (Universidade Federal de São Carlos, 2026)
This dissertation examines vulnerabilities and public participation in Health Technology Assessment (HTA) processes conducted by the National Committee for Health Technology Incorporation (CONITEC) in the Brazilian Unified Health System (SUS), with emphasis on rare diseases. A total of 83 technical reports issued between 2015 and 2024 were analyzed using a qualitative approach based on documentary analysis, systematic organization of data, and content analysis of contributions submitted during public consultations. The findings, interpreted through the lenses of Science, Technology and Society (STS) studies and bioethics, reveal that the vulnerabilities of patients and family members emerge in multiple dimensions—physical, emotional, social, economic, and related to access barriers—and appear frequently within public consultation inputs. The analysis shows that such vulnerabilities exert a real but not decisive influence on the modification of preliminary recommendations: they enhance the social legitimacy of the process and enrich the understanding of the disease context, but only lead to recommendation changes when aligned with additional clinical evidence, reduced methodological uncertainty, or economic negotiations that make the technology viable for the health system. Thus, economic considerations and the robustness of scientific evidence remain the central determinants of decision-making, whereas vulnerabilities function as interpretive and ethical elements that expand moral sensitivity but do not operate as autonomous criteria. The study concludes that, although public participation within CONITEC has advanced, challenges remain regarding the effectiveness of contributions and the systematic consideration of equity. This dissertation contributes to the STS field by problematizing the social construction of health technology decisions and by reinforcing the need to integrate bioethical principles into policies for rare diseases.
Bioethics, vulnerabilities, and social participation in health technology assessment: an analysis of CONITEC decisions on rare diseases
Keywords: Doenças Raras; CONITEC; Avaliação de Tecnologias em Saúde; Bioética; Vulnerabilidades; Participação Social; Rare Diseases; CONITEC; Assessment of Health Technologies; Bioethics; Vulnerabilities; Public Participation; CIENCIAS HUMANAS; 10. Redução das Desigualdades; 16. Paz, Justiça e Instituições Eficazes; 3. Saúde e Bem-Estar